1989
DOI: 10.3109/00016358909007715
|View full text |Cite
|
Sign up to set email alerts
|

Craniomandibular disorders and general joint mobility

Abstract: The purpose of the investigation was to study the relationship between general joint mobility and dysfunction among patients with craniomandibular disorders (CMD). Joint mobility was assessed in 74 female patients and 73 controls, using Beighton's modification of the Carter & Wilkinson hypermobility score. Twenty-five (83%) of 30 patients with score greater than or equal to 3 (lax joints) had temporomandibular joint (TMJ) involvement. Eighteen (41%) of 44 patients with score 0-2 (no laxity) had TMJ involvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…This suggestion is supported by the positive correlation found between hypermobility of the TM joint, scored using double‐contrast arthrotomograms, and disc displacements . Although not undisputed , a number of studies have also reported that generalised joint hypermobility, graded by means of the hypermobility score of Beighton , is a risk factor for symptoms of TMD (muscle and joint pain and TM‐joint clicking sounds) . However, when the focus was not on the association with clicking sounds but on that with disc displacements, studies came to contradictory results.…”
Section: Resultsmentioning
confidence: 99%
“…This suggestion is supported by the positive correlation found between hypermobility of the TM joint, scored using double‐contrast arthrotomograms, and disc displacements . Although not undisputed , a number of studies have also reported that generalised joint hypermobility, graded by means of the hypermobility score of Beighton , is a risk factor for symptoms of TMD (muscle and joint pain and TM‐joint clicking sounds) . However, when the focus was not on the association with clicking sounds but on that with disc displacements, studies came to contradictory results.…”
Section: Resultsmentioning
confidence: 99%
“…Despite this, it is difficult to compare the findings with previously reported figures on sex and age distribution because the ethnic differences may be considerable. Only one Scandinavian investigation of a non-patient group is available (17). In that investigation of 73 women between 17 and 35 yr of age, 30% had a score of > 3 and 12% had a score of >4.…”
Section: Discussionmentioning
confidence: 99%
“…There are certainly also other factors that induce headache in CMD patients. One such factor may be impaired TMJ function which mainly occurred in individuals with lax joints (17).…”
Section: Discussionmentioning
confidence: 99%
“…The questions about occurrence of headache once or more a week and occurrence of trauma to the head and jaws had to be answered by 'yes' or 'no'. 7 All adolescents were clinically examined by examiner A before any information about their history was obtained. No radiographic investigation of the TMJ was performed.…”
Section: Subjectsmentioning
confidence: 99%